Analysis of the success factors for MSME succession in Surabaya: A principal component analysis - Candraningrat .; Oktaviani .; Sri - Suhandiah (Journal of Economics, Business, and Accountancy Ventura, 2018)
This study aims to find success factors for succession in family-based MSMEs in MSMEs in Surabaya, Indonesia, where Surabaya is a metropolitan city that allows entrepreneurs to develop and be sustainable for the next generation of family businesses. The research method used is factor analysis which is an analysis technique that forms the latent variables that have not been determined before the analysis, the results of anilisation will find any factors that influence the success of succession in MSMEs. Sample in this study amounted to 100 MSMEs of family businesses that could be met in Surabaya or incidental sampling, while respondents in this study were second generation family business owners. The method of data collection is a survey with a questionnaire instrument that has been tested for validity and reliability. The data analysis technique used is the Principal Component Analysis Factor Analysis with SPSS software. The results of this study found that six factors that determine the success of succession in MSMEs in the city of Surabaya are succession preparation procedures, successor characteristics, readiness of previous generations, communication in the succession process, relationships between family members, and introduction to the business environment. This research is expected to provide references on the sustainability of family business to the next generation in the city of Surabaya, East Java, Indonesia.